Microbicidal Phagocytosis of Nucleus Pulposus Cells Against Staphylococcus aureus via the TLR2/MAPKs Signaling Pathway - Lin, Yazhou; Cong, Hui; Liu, Kewei; Jiao, Yucheng; Yuan, Ye; Tang, Guoqing; Chen, Yong; Zheng, Yuehuan; Xiao, Jiaqi; Li, Changwei; Chen, Zhe; Cao, Peng (Frontiers in Immunology, 2019)
Intervertebral disc (IVD) is an immune-privilege organ that lacks immunocytes, such as macrophages or neutrophils; therefore, it is unclear how IVD immunological defense against bacterial infection occurs. Here, we demonstrated that nucleus pulposus cells (NPCs), the vital machinery for maintaining the homeostasis of IVD, exerted microbicidal activity against Staphylococcus aureus via induction of phagolysosome formation. Moreover, we found that the Toll-like receptor 2 (TLR2)/mitogen-activated protein kinases (MAPKs) signaling pathway is critical for bacterial phagocytosis and phagolysosome formation of NPCs. These findings demonstrated for the first time that NPCs could function as non-professional phagocytes against S. aureus infection, thereby enhancing antimicrobial defense against bacterial infections in IVDs.